The effects of Salvia przewalskii total phenolic acid extract on immune complex glomerulonephritis - Yang Yang; Zhi-Peng Wang; Shou-Hong Gao; Hong-Qi Ren; Ren-Qian Zhong; Wan-Sheng Chen (Taylor & Francis Group, 2017)
Context: Salvia przewalskii Maxim. (Lamiaceae) is a Chinese herbal medicine that has long been used for the treatment of cardiovascular disease. Objective: The study investigated the therapeutic efficacy of S. przewalskii total phenolic acid extract (SPE) on immune complex glomerulonephritis (ICG) in rats. Materials and methods: Sixty-two Wistar rats were randomized into six groups. ICG was induced in all groups except normal control group. SPE was administered intragastrically at 24 h intervals for 40 consecutive days. Urine protein (UP), total serum protein (TSP), serum albumin (SA), serum cholesterol (SC) and serum urea nitrogen (SUN) were measured one day before, on day 20 and 40 after SPE administration. On day 40 after SPE administration, the kidneys were removed and prepared into pathologic sections. In addition, kidney wet mass was measured for calculating the kidney wet mass coefficient (KWMC). Results: UP excretion was reduced significantly on day 20 after SPE administration in all three SPE groups as compared with that in medium group, and this effect was observable continuously until 40 days after SPE administration. Compared with medium group, TSP and SA were increased in all three SPE groups after 40 days treatment, while SC and SUN were decreased. KWMC was decreased significantly in 100 mg/kg SPE group after 40 days treatment compared with that in medium group. Histopathologic analyses showed that renal inflammatory infiltration and kidney intumesce were alleviated in all three SPE groups. Conclusions: SPE may be a potential therapeutic drug for glomerulonephritis.